Economic development and the use of energy resources in Communist China - Wu, Yuan-li. (New York: Frederick A. Praeger, 1963)
The Hoover Institution on war, revolution, and peace is concerned primarily with promoting basic research and documentary studies and with investigating topics where the findings can make important contributions to national policy. For this reason, the institution decided to concentrate one part of the program on international communism.
Bibliographical references included in "Notes" (p. 242-271)
ne 11/04/2018
Loans
Keywords: Power resources; Energy resources; Economic development; Communist China